Потенциал развития «зеленого сектора» промышленности Украины - Заниздра, М.Ю. (Економіка промисловості, 2017)
Обобщена структура спроса и предложения товаров и услуг «зеленого» рынка. Проведен анализ текущего экономико-экологического профиля Украины согласно «12 составляющим» индекса глобальной конкурентоспособности, уровня техногенной нагрузки, институциональных особенностей управления в сфере специального природопользования. Обоснован подход к оценке потенциала развития «зеленого сектора» промышленности в Украине. Узагальнено структуру попиту та пропозиції товарів і послуг «зеленого» ринку. Виконано аналіз поточного економіко-екологічного профілю України відповідно до «12 складових» індексу глобальної конкурентоспроможності, рівня техногенного навантаження, інституційних особливостей управління у сфері спеціального природокористування. Обґрунтовано підхід до оцінки потенціалу розвитку «зеленого сектору» промисловості в Україні. Based on the analysis of the Global Competitiveness Index, Ecological Footprint and Biological Capacity, Investment Ratio author observed low competitiveness and investment activity as well as environmental challenges of the Ukrainian economy. Analysis of existing approaches to estimating the size of green markets was conducted. The structure of goods and services’ supply and demand, agents of influence and development drivers of the «green» market are summarized. Background, that maximize the potential for the development of the «green sector» of industry; was defined: rapid industrialization; strict environmental legislation; high requirements to the environmental quality of the product life cycle; high level of an intellectual capital development, access to markets of economies with a high level of industrialization; low level of intellectual capital development and low biological capacity; access to ecosystems with a high biological capacity. Approach to the assessment of the development potential of the «green sector» of industry in Ukraine have been offered.The basis for the calculation of adopted indicators: the total volume of capital investments and current expenditures for protection and rational use of natural resources; the environmental taxes; the price of specific natural resources; the funds received from land sale and greenhouse gases’ emissions trading schemes, also provision of services in the field of energy from renewable sources (nominally «green» energy), water and wastewater, waste management. An assessment of the «green» market of Ukraine as of 2015 was received. It amounted to UAH 65.7 bn. Given that a number of indicators were not taken into account, this assessment can be considered as a minimum capacity of the «green» sector of the industry. In particular, due to the lack of statistical monitoring for the specific types of economic activity, sales of professional services of environmental audit, insurance and other environmentally oriented services, provided by private enterprises, were not taken into account.Prospects for further research are: refinement of the methodology for assessing the«green» market capacity, substantiation the set of key indicators, development of recommendations on reforming statistical reporting forms of enterprises, that would allow to monitor ecologically-oriented entrepreneurial activities according to the sectors of the green industry («sector of environmental goods and services», «green business», «economic entities, that use green solutions»).